Fault-tolerant control scheme for modular multilevel converter based on sorting algorithm without reserved submodules - Kim, Seok Min; Lee, Kyo Beum; Lee, June Seok (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2018)
This paper proposes a fault-tolerant method for the half-bridge based modular multilevel converter (MMC). Fault-tolerance is able to enhance reliability which is one of the crucial issue for the MMC with a large number of switching devices. In this paper, the faulty condition of the MMC is analyzed and the detail of the proposed fault-tolerant method is described. When a switching device fault is occurred in a SM, the proposed method balances the three-phase line-to-line voltages and currents and does not require redundant submodules (SMs), which reduce the cost and volume of the MMC. To verify the fault-tolerant ability of the proposed method, various simulation results are included.
Keywords: Fault tolerant ability; Fault tolerant control; Fault-tolerant method; Modular multi-level converters; Sorting algorithm; Submodules; Switching devices; Three-phase lines; Fault-tolerant control; Half-bridge submodule; Modular multilevel converter (MMC); Reliability; Sorting algorithm